Mechanical behavior of structural concrete with electric arc furnace slag and rice husk ash as a replacement for cement under normal conditions - Quispe, Ana Margot Castro (2024)
The steel industry is responsible for producing large volumes of electric arc furnace slag. This by-product has no use or benefit for these companies, so they proceed to discard them. However, there are companies that choose to dispose these by-products improperly due to the high cost of treating the slag to avoid any type of contamination. Similarly, the agricultural industry is responsible for producing and disposing more than 300 000 tons of rice husks annually. These factors are the main reason for the recycling of both by-products in the construction sector. The objective of this research is to evaluate the mechanical behavior of structural concrete with the partial replacement of cement by electric arc furnace slag and rice husk ash. For this purpose, a master mix and four mix designs with replacement proportions of 7.5% and 12.5% of electric arc furnace slag are prepared; and 5% and 7.5% rice husk ash. The chemical composition of both pozzolans is evaluated by Fluorescence and X-Ray Diffraction tests. In addition, compressive, flexural and tensile strength tests are carried out to evaluate the mechanical properties. The results indicate a better resistance to compression when using both pozzolans as a replacement for cement for concrete designs f'c 210. Likewise, in the flexural tests, the mixtures with pozzolans display a good behavior when compared to the standard mixture.